Determination of isokinetic strength of upper and lower body of elite male boxers - Aktas, S.; Tatlici, A.; Cakmakci, O. (Turkish Journal of Sport and Exercise, 2019)
It is well known that punching force is highly important to boxers for winning and one of the key component of amateur boxing. Boxing needs also get blocking position, after throwing a punch to not receive a punch. The aim of the study was to determine thedominant internal-external shoulder muscles and dominant extension-flexion leg muscles strength of the elite boxers at 60° and 180° sec-1. In the study, 10 male elite boxers 22.10 ± 1.37 years, height 174.60 ± 6.41 cm and 72.60 ± 10.74 kg participated in the study. The isokinetic knee and shoulder strength tests were performed with an isokinetic dynamometer (Cybex, Humac Norm 2004) in the kinanthropometry laboratory of Selcuk University. Statistical analysis of the data was performed using SPSS 22 package program. Descriptive data of the participants were given as mean, minimum, maximum and standard deviation. it was determined that the peak dominant leg strength of elite boxers were found for extension 224,900 nM (60 °/s) and 135,70 nM (180 °/s ). The peak dominant leg strength of elite boxers found for flexion 120,50 nM and 72,30 nM at 60 °/s and 180 °/s respectively. Elite boxers` leg strength was similar to literatür. As a result of the study, it can be said that the internal muscle group of boxers produce more power than external muscle group. It can be concluded that the boxers have better punching strength than defense.